Penyuluhan Senam Osteoporosis sebagai pencegahan Osteoporosis - Idahwati, Idahwati; Sijabat, Flora; Sinuraya, Elida; Halawa, Theresia; Nduru, Christian; Sianturi, Juyanti; Simamora, Rosmayana; Simatupang, Agnes Theresia; Sipayung, Lia Nurhayati (Kolaborasi: Jurnal Pengabdian Masyarakat, 2024)
Introduction: Low physical activity in society has an impact on increasing cases of osteoporosis. This makes bones break easily and causes pain, impaired movement and decreased productivity. Therefore, it is important to make efforts to prevent osteoporosis, such as physical exercise: osteoporosis exercises. Objective: The purpose of this service was to increase the understanding of elderly people about osteoporosis exercises to prevent osteoporosis Method: The method used was lecture and demonstrations about osteoporosis exercise. This public service was conducted by lecturers and students at the Nursing Diploma, Sari Mutiara University Indonesia Result: about 80% of elderly people were understand and able to demonstrate about osteoporosis exercises. Conclusion: After receiving teaching, elderly people's knowledge about osteoporosis exercise as a prevention of osteoporosis has increased.